2011
DOI: 10.1128/jvi.00182-11
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Zta-Induced Immunomodulators from Nasopharyngeal Carcinoma Cells Upregulate Interleukin-10 Production from Monocytes

Abstract: During lytic infection with Epstein-Barr virus (EBV), several viral lytic proteins function to evade immune recognition or to actively suppress immune cells. An EBV lytic transactivator, Zta, induces an immunosuppressive cytokine interleukin 10 (IL-10) in B cells, but whether it regulates IL-10 in the context of epithelial cells is unclear. In this study, we tested nasopharyngeal carcinoma (NPC) cell lines and found that Zta did not induce IL-10 in these epithelial cells. Interestingly, the conditioned medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 61 publications
(75 reference statements)
1
36
0
Order By: Relevance
“…In a few instances, viral proteins have been shown to stimulate activation of the COX/PGE 2 pathway, often by acting either directly or indirectly as a transcriptional transactivator of COX-2 gene expression (3639). Among the viral proteins for which this activity has been reported, the hepatitis C virus (HCV) protein NS3, a viral serine protease, is known to enhance the COX-2/PGE 2 pathway by activating multiple signaling pathways (40).…”
Section: Discussionmentioning
confidence: 99%
“…In a few instances, viral proteins have been shown to stimulate activation of the COX/PGE 2 pathway, often by acting either directly or indirectly as a transcriptional transactivator of COX-2 gene expression (3639). Among the viral proteins for which this activity has been reported, the hepatitis C virus (HCV) protein NS3, a viral serine protease, is known to enhance the COX-2/PGE 2 pathway by activating multiple signaling pathways (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of Zta to the target promoter was detected by using the ChIP assay as described in our previous study [37]. Zta was immunoprecipitated by using a mouse monoclonal antibody AZ-69 (Argene, Varilhes, France).…”
Section: Methodsmentioning
confidence: 99%
“…During lytic reactivation EBV transactivator protein Zta helps to evade immune surveillance. EBV Zta has been shown to enhance the activity of COX-2 promoter thereby upregulating the production of COX-2 and its downstream effector molecule PGE 2 (Lee et al, 2011). It has also been shown that EBV could suppress PGE 2 biosynthesis in LPS-activated monocytes (Savard et al, 2000).…”
Section: Ebv Infection Is Often Associated With Elevated Expression Omentioning
confidence: 99%
“…Both LPS treatment and EBV infection did not affect COX-1 levels, indicating COX-2 as the major isoform involved in inflammatory stimuli induced PG synthesis in presence of EBV infection. However, a separate study showed that conditioned medium of Zta-expressing NPC cells enhances IL-10 production from monocytes which was mediated in part by elevated COX-2 levels in NPC cells (Lee et al, 2011). It has been speculated that the IL-10 production in monocytes may play role in facilitating local microenvironment in favor of immunosuppression (Lee et al, 2011).…”
Section: Ebv Infection Is Often Associated With Elevated Expression Omentioning
confidence: 99%